A Hierarchical Structured Ultrafine Fiber Device for Preventing Postoperative Recurrence and Metastasis of Breast Cancer. (9th September 2020) - Li, Xilin; Xu, Funeng; He, Yang; Li, Yan; Hou, Jianwen; Yang, Guang; Zhou, Shaobing
Abstract: The high incidence of postoperative recurrence and metastasis has a serious effect on survival in breast cancer patients. Moreover, it is still a great challenge to prevent the postoperative recurrence and metastasis through traditional implantable devices due to their inability to control multiple drug release. Herein, an implantable hierarchical structured ultrafine fiber device with a time‐programmed drug release function for the local postoperative adjuvant chemotherapy of breast cancer is developed. The structure is obtained through a co‐axial electrospinning technology by the formation of the periodically arranged chambers inside a fiber matrix. The Doxorubicin hydrochloride in these chambers is released rapidly, killing the residual tumor cells to prevent tumor recurrence; while the matrix metalloproteinases‐2 (MMP‐2) inhibitor disulfiram in the fiber matrix is released in a sustained manner, inhibiting tumor invasion to prevent its metastasis. The fiber device implanted in tumor‐bearing mice after a surgical tumor reduction displays excellent therapeutic efficacy by preventing both recurrence and metastasis. The mechanism investigation of tumor invasion through the type‐II collagen immunofluorescence analysis reveals that the decrease of the activity of MMP‐2 plays a key role in this process. Abstract : An implantable hierarchical structured ultrafine fiber device is successfully developed through a co‐axial electrospinning technology. This device can significantly improve the effectiveness of surgical intervention via a time programmed dual drug release by reducing the risk of cancer recurrence and metastasis after primary tumor resection.